Studies on the vignettes from chapter 17 of the Book of the dead : I : the image of mś.w Bdšt in ancient Egyptian mythology /: I : the image of mś.w Bdšt in ancient Egyptian mythology. ([2016]) - Tarasenko, Nikolaĭ
No abstract available